The Effect of Problem-based Learning Model on the Fourth-Grade Elementary Students' Learning Outcomes - Saguruh Melky Sedek Simare-Mare; Patri Janson Silaban; Rumiris Lumban Gaol; Nova Florentina Ambarwati; Antonius Remigius Abi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the effect of the problem-based learning model on students’ learning outcomes in theme 8 of the area where I live in class IV SD. The study in this paper uses associative quantitative methods. The research population involves 31 fourth-grade students at SD Negeri 065013 Tanjung Sari Medan. The sampling uses a purposive sample and there are 31 students. The results indicate that students’ learning outcomes using the problembased learning model are included in the good category with an average of 78.19 with a correlation test result of 0.977, which means rcount 0.977 ≥ rtable 0.355, then Ha is accepted. Therefore, there is a significant effect between the use of the problem-based learning model on students’ learning outcomes on the theme of the area where I live in class IV SD Negeri 065013 Tanjung Sari Medan. It can be seen from the results of the T-test where tcount 24.598 ≥ ttable 2.045 so that Ha is accepted. As a result, there is a significant positive effect from the use of the problem-based learning model on student’s learning outcomes in theme 8 of the area where I live in class IV SD Negeri 065013 Tanjung Sari Medan in the academic year 2022/2023